The impact of traffic congestions on tourist behavior: Case study of Chiang Mai, Thailand - Chong, Daniel Ka Leong * (2016)
Traffic congestions in major cities of Thailand is a persistent issue to foreign tourists. 2 major cities, Bangkok and Chiang Mai were perceived the most congested cities in Thailand. However, Chiang Mai was considered the worst due to poor public transportation systems as compared to Bangkok. This research aim to explore the condition and the impacts of traffic congestion on tourist attitude pertaining to travelling within Chiang Mai. Qualitative approach was used in this research. Interviews and site observations were conducted as the form of data collection. ABC Models of Attitudes was used as an approach to assists questionnaire development for interview. While, bottleneck approach which relates to demand exceeding capacity in a punctual location by TRB (2000) was used as the congestion indicator in site observation. Past literatures concerning tourist behaviour and traffic congestion in tourist area were incorporated to triangulate and to support the data gathered. The findings denote that the foreign tourists perceived negatively towards the traffic congestion in Chiang Mai. This perception have led them to prefer destinations that are away from traffic and within walking distance from their accommodations.